Stakeholder analysis to guide co-production of nature-based solutions to address livelihood vulnerability: the case of Dolo Ado and Bokolmayo districts, Somali Regional State, Ethiopia - Mekuria, Wolde; Dessalegn, Mengistu; Ebrahim, Girma Yimer; Tegegne, Desalegn; Haile, Alemseged Tamiru; Ruckstuhl, Sandra (International Water Management Institute (IWMI). CGIAR Initiative on Fragility, Conflict, and Migration, 2024)
We conducted stakeholder mapping and analysis in the Dolo Ado and Bokolmayo districts in the Somali Regional State of Ethiopia to improve our understanding of how to co-create and co-plan nature-based solutions (NbS) to address the vulnerability of displaced people and host communities to natural hazards such as floods and drought. Diverse stakeholders such as government development agencies, nongovernmental organizations (NGOs), research and development institutions, international humanitarian entities, the private sector, communities and community-based organizations participate in the planning, design and implementation of NbS in multiple ways. The modes of their participation include provision of expertise, material and financial support, community mobilization, implementation of interventions, and monitoring and evaluation. Our analysis found that most of the stakeholders have strong perceived legitimacy in their field of endeavor. This facilitates access to political support and helps in the mobilization of local communities.